Wet-type plastic refractory for copper smelting system and preparation method of wet-type plastic refractory

By preparing a wet plastic for copper smelting system with a specific ratio and adopting a specific mixing and stirring process, the existing wet plastics are solved, and the effects of insufficient thermal shock resistance and prone to cracking are achieved, achieving high durability and long service life.

CN119591414APending Publication Date: 2025-03-11YUNNAN KUNSTEEL GRP REFRACTORY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411872012.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The wet plastics used in existing copper smelting systems are insufficient in thermal shock resistance and are prone to cracking during use, resulting in low durability and short service life.

Method used

By preparing a wet plasticizer for copper smelting system including 60 to 70 parts of pellet mixture, 35 to 45 parts of fine powder mixture, 10 to 18 parts of composite plasticizing solvent, 5 to 12 parts of binder and 0.5 to 3 parts of explosion-proof agent, a specific mixing and stirring process is adopted to form a high-density, wear-resistant and erosion-resistant ceramic body.

Benefits of technology

The wet plastic has high strength, wear resistance, thermal shock stability and corrosion resistance, which effectively extends the service life, improves physical performance, and reduces maintenance frequency and losses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a wet-type plastic material for a copper smelting system and a preparation method thereof, and the wet-type plastic material for the copper smelting system comprises the following raw materials in parts by weight: 60-70 parts of a particle mixture, 35-45 parts of a fine powder mixture, 10-18 parts of a composite plasticizing solvent, 5-12 parts of a binding agent and 0.5-3 parts of an anti-explosion agent. The preparation method of the wet-type plastic refractory for the copper smelting system comprises the following steps: firstly, preparing the particle mixture, the fine powder mixture, the composite plasticizing solvent and the binding agent, then uniformly stirring the raw material mixtures, and mixing and grinding the raw material mixtures into cement. The plastic material has the advantages of high strength, wear resistance, thermal shock resistance and good corrosion resistance, the physical properties of the plastic material are effectively improved, cracks are not easy to generate, and the service life is effectively prolonged; and construction is convenient, long-time storage can be achieved, the maintenance frequency and loss of the copper melting furnace lining can be reduced, and production economic benefits are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials for copper smelting systems, and in particular to a wet plastic material for copper smelting systems and a preparation method thereof. Background Art

[0002] A copper melting furnace is a device used for smelting copper. Its working temperature is generally around 1200℃, and it requires high-temperature resistant materials as furnace linings. However, wet plastics can form a solid ceramic body after drying and sintering due to their plasticity and formability, thus having the characteristics of high temperature resistance, corrosion resistance, and wear resistance. They are usually used as the linings of copper melting furnaces. The ceramic body formed by sintering existing wet plastics is prone to insufficient thermal shock resistance and cracking during use, and has low durability and short service life.

[0003] Therefore, developing a wet plastic material for copper melting furnace that can effectively extend service life is the key to solving the problem. Summary of the invention

[0004] The object of the present invention is to provide a wet plastic material for copper smelting system and a preparation method thereof in view of the deficiencies of the prior art.

[0005] To achieve the above-mentioned purpose, the present invention is implemented through the following technical scheme: in parts by weight, the wet plastic material for copper smelting system includes the following raw materials: 60-70 parts of granular mixture, 35-45 parts of fine powder mixture, 10-18 parts of composite plasticizing solvent, 5-12 parts of binder, and 0.5-3 parts of explosion-proof agent.

[0006] The method for preparing the wet plastic material for the copper smelting system described in the present invention comprises the following steps: A. Preparation of particle mixture: add alumina with a particle size of 3-1 mm and alumina with a particle size of 0.1-1 mm into a mixer and grind for 1-2 minutes for later use; B. Preparation of fine powder mixture: add super-grade bauxite powder, plate-shaped corundum powder, Guangxi white mud, bentonite powder, alumina powder and silicon carbide powder into a mixer and grind for 1-2 minutes for later use; C. Preparation of composite plasticizer solvent: Take room temperature water with 25% plasticizer solvent and add sodium tripolyphosphate, dextrin and benzoic acid in a container in turn, and stir until dissolved; secondly, add carboxymethyl cellulose and stir for 10-20 minutes, stir evenly, add boiling water with 63% plasticizer solvent, stir rapidly for 30-50 minutes until paste, cool for 1-2 hours, and set aside; D. Preparation of binder: put ethylene glycol in a container, add phenolic resin while stirring until the solution is uniform, and set aside; E. Preparation of wet plastic: first place the granular mixture obtained in step A in a planetary mixer, add 30% to 40% of the total amount of the composite plasticizer solvent obtained in step C while stirring, then add 28 to 32% of the total amount of the binder obtained in step D and continue stirring for 2 to 3 minutes, then add the fine powder mixture obtained in step B and stir for 1 to 2 minutes, finally add the remaining composite plasticizer solvent and binder in turn, mix and grind for 10 to 15 minutes into a paste state, and thus obtain the wet plastic.

[0007] The beneficial effects of the present invention include: high strength, good wear resistance, thermal shock stability and corrosion resistance; aggregates of different particle sizes work together with other micropowders to form a denser plastic material, which improves wear resistance and corrosion resistance, effectively improves the physical properties of the plastic material and is less likely to crack, thereby effectively extending the service life; on the other hand, the addition of a plasticizer improves the plasticity of the wet plastic material, making construction more convenient; the sintering agent improves the sintering quality of the wet plastic material and further improves the physical properties; the preservative can extend the shelf life to 6 months, which is beneficial to reducing the maintenance frequency and loss of the copper melting furnace lining and improving production economic benefits. DETAILED DESCRIPTION

[0008] The present invention will be further described below in conjunction with the embodiments, but is not limited to the contents of the description.

[0009] A wet plastic material for a copper smelting system comprises the following raw materials, measured by weight: 60-70 parts of a granular mixture, 35-45 parts of a fine powder mixture, 10-18 parts of a composite plasticizing solvent, 5-12 parts of a binder, and 0.5-3 parts of an explosion-proof agent.

[0010] The particle mixture is a mixed alumina with Al2O3≥85%, and the mixed alumina includes 30-35 parts of alumina with a particle size of 3-1 mm and 28-32 parts of alumina with a particle size of 0.1-1 mm.

[0011] The fine powder mixture comprises: 11-13 parts of alumina powder, 11-13 parts of plate-shaped corundum powder, 5-8 parts of Guangxi white mud, 3-5 parts of bentonite powder, and 2-4 parts of alumina micropowder.

[0012] The alumina powder particle size is ≤74μm, the plate-shaped corundum powder particle size is ≤44μm, the Guangxi white mud and bentonite powder particle size is ≤74μm, the alumina powder Al2O3 is ≥99%, and the particle size D50, μm requirement is 2.3±0.5.

[0013] The explosion-proof agent is explosion-proof fiber with a melting point of ≤105°C.

[0014] The composite plasticizing solvent comprises 88 parts of water, 4-5 parts of carboxymethyl cellulose, 4-5 parts of sodium tripolyphosphate, 1-2 parts of dextrin and 1-2 parts of benzoic acid.

[0015] The binder comprises 33 parts of phenolic resin and 67 parts of ethylene glycol.

[0016] The fine powder mixture also includes 10 to 18 parts of silicon carbide powder.

[0017] The method for preparing wet plastic material for copper smelting system comprises the following steps: A. Preparation of particle mixture: add alumina with a particle size of 3-1 mm and alumina with a particle size of 0.1-1 mm into a mixer and grind for 1-2 minutes for later use; B. Preparation of fine powder mixture: add super-grade bauxite powder, plate-shaped corundum powder, Guangxi white mud, bentonite powder and alumina powder into a mixer and grind for 1-2 minutes for later use; C. Preparation of composite plasticizer solvent: Take room temperature water with 25% plasticizer solvent and add sodium tripolyphosphate, dextrin and benzoic acid in a container in turn, and stir until dissolved; secondly, add carboxymethyl cellulose and stir for 10-20 minutes, stir evenly, add boiling water with 63% plasticizer solvent, stir rapidly for 30-50 minutes until paste, cool for 1-2 hours, and set aside; D. Preparation of binder: put ethylene glycol in a container, add phenolic resin while stirring until the solution is uniform, and set aside; E. Preparation of wet plastic: first place the granular mixture obtained in step A in a planetary mixer, add 30% to 40% of the total amount of the composite plasticizer solvent obtained in step C while stirring, then add 28 to 32% of the total amount of the binder obtained in step D and continue stirring for 2 to 3 minutes, then add the fine powder mixture obtained in step B and stir for 1 to 2 minutes, finally add the remaining composite plasticizer solvent and binder in turn, mix and grind for 10 to 15 minutes into a paste state, and thus obtain the wet plastic.

[0018] Example 1

[0019] A wet plastic material for a copper smelting system comprises the following raw materials by weight: 60 parts of a granular mixture, which is prepared by mixing alumina with Al2O3≥85% and particle sizes of 3-1mm and 0.1-1mm; 35 parts of a fine powder mixture, which is prepared by mixing alumina powder with a particle size of ≤74μm, plate-shaped corundum powder with a particle size of ≤44μm, Guangxi white mud and bentonite powder with a particle size of ≤74μm, and alumina micropowder with Al2O3≥99% and a particle size D50, μm required to be 2.3±0.5; 10 parts of a composite plasticizing solvent, which is prepared by mixing water, carboxymethyl cellulose, sodium tripolyphosphate, dextrin and benzoic acid; 5 parts of a binder, which is prepared by mixing phenolic resin and ethylene glycol; and 0.5-3 parts of an explosion-proof agent.

[0020] A method for preparing a wet plastic material for a copper smelting system comprises the following steps: A. Preparation of particle mixture: add alumina with a particle size of 3-1 mm and alumina with a particle size of 0.1-1 mm into a mixer and grind for 1-2 minutes for later use; B. Preparation of fine powder mixture: add super-grade bauxite powder, plate-shaped corundum powder, Guangxi white mud, bentonite powder and alumina powder into a mixer and grind for 1-2 minutes for later use; C. Preparation of composite plasticizer solvent: Take room temperature water with 25% plasticizer solvent and add sodium tripolyphosphate, dextrin and benzoic acid in a container in turn, and stir until dissolved; secondly, add carboxymethyl cellulose and stir for 10-20 minutes, stir evenly, add boiling water with 63% plasticizer solvent, stir rapidly for 30-50 minutes until paste, cool for 1-2 hours, and set aside; D. Preparation of binder: put ethylene glycol in a container, add phenolic resin while stirring until the solution is uniform, and set aside; E. Preparation of wet plastic: first place the granular mixture obtained in step A in a planetary mixer, add 30% to 40% of the total amount of the composite plasticizer solvent obtained in step C while stirring, then add 28 to 32% of the total amount of the binder obtained in step D and continue stirring for 2 to 3 minutes, then add the fine powder mixture obtained in step B and stir for 1 to 2 minutes, finally add the remaining composite plasticizer solvent and binder in turn, mix and grind for 10 to 15 minutes into a paste state, and thus obtain the wet plastic.

[0021] Example 2

[0022] A wet plastic material for a copper smelting system comprises the following raw materials by weight: 65 parts of a granular mixture, which is prepared by mixing alumina with Al2O3≥85% and particle sizes of 3-1mm and 0.1-1mm; 40 parts of a fine powder mixture, which is prepared by mixing alumina powder with a particle size of ≤74μm, plate-shaped corundum powder with a particle size of ≤44μm, Guangxi white mud and bentonite powder with a particle size of ≤74μm, and alumina micropowder with Al2O3≥99% and a particle size D50, μm required to be 2.3±0.5; 14 parts of a composite plasticizing solvent, which is prepared by mixing water, carboxymethyl cellulose, sodium tripolyphosphate, dextrin and benzoic acid; 8 parts of a binder, which is prepared by mixing phenolic resin and ethylene glycol; and 1.5 parts of an explosion-proof agent.

[0023] A method for preparing a wet plastic material for a copper smelting system comprises the following steps: A. Preparation of particle mixture: add alumina with a particle size of 3-1 mm and alumina with a particle size of 0.1-1 mm into a mixer and grind for 1-2 minutes for later use; B. Preparation of fine powder mixture: add super-grade bauxite powder, plate-shaped corundum powder, Guangxi white mud, bentonite powder and alumina powder into a mixer and grind for 1-2 minutes for later use; C. Preparation of composite plasticizer solvent: Take room temperature water with 25% plasticizer solvent and add sodium tripolyphosphate, dextrin and benzoic acid in a container in turn, and stir until dissolved; secondly, add carboxymethyl cellulose and stir for 10-20 minutes, stir evenly, add boiling water with 63% plasticizer solvent, stir rapidly for 30-50 minutes until paste, cool for 1-2 hours, and set aside; D. Preparation of binder: put ethylene glycol in a container, add phenolic resin while stirring until the solution is uniform, and set aside; E. Preparation of wet plastic: first place the granular mixture obtained in step A in a planetary mixer, add 30% to 40% of the total amount of the composite plasticizer solvent obtained in step C while stirring, then add 28 to 32% of the total amount of the binder obtained in step D and continue stirring for 2 to 3 minutes, then add the fine powder mixture obtained in step B and stir for 1 to 2 minutes, finally add the remaining composite plasticizer solvent and binder in turn, mix and grind for 10 to 15 minutes into a paste state, and thus obtain the wet plastic.

[0024] Example 3

[0025] A wet plastic material for a copper smelting system comprises the following raw materials by weight: 70 parts of a granular mixture, which is prepared by mixing alumina with Al2O3≥85% and particle sizes of 3-1mm and 0.1-1mm; 45 parts of a fine powder mixture, which is prepared by mixing alumina powder with a particle size of ≤74μm, plate-shaped corundum powder with a particle size of ≤44μm, Guangxi white mud and bentonite powder with a particle size of ≤74μm, and alumina micropowder with Al2O3≥99% and a particle size D50, μm required to be 2.3±0.5; 18 parts of a composite plasticizing solvent, which is prepared by mixing water, carboxymethyl cellulose, sodium tripolyphosphate, dextrin and benzoic acid; 12 parts of a binder, which is prepared by mixing phenolic resin and ethylene glycol; and 3 parts of an explosion-proof agent.

[0026] A method for preparing a wet plastic material for a copper smelting system comprises the following steps: A. Preparation of particle mixture: add alumina with a particle size of 3-1 mm and alumina with a particle size of 0.1-1 mm into a mixer and grind for 1-2 minutes for later use; B. Preparation of fine powder mixture: add super-grade bauxite powder, plate-shaped corundum powder, Guangxi white mud, bentonite powder and alumina powder into a mixer and grind for 1-2 minutes for later use; C. Preparation of composite plasticizer solvent: Take room temperature water with 25% plasticizer solvent and add sodium tripolyphosphate, dextrin and benzoic acid in a container in turn, and stir until dissolved; secondly, add carboxymethyl cellulose and stir for 10-20 minutes, stir evenly, add boiling water with 63% plasticizer solvent, stir rapidly for 30-50 minutes until paste, cool for 1-2 hours, and set aside; D. Preparation of binder: put ethylene glycol in a container, add phenolic resin while stirring until the solution is uniform, and set aside; E. Preparation of wet plastic: first place the granular mixture obtained in step A in a planetary mixer, add 30% to 40% of the total amount of the composite plasticizer solvent obtained in step C while stirring, then add 28 to 32% of the total amount of the binder obtained in step D and continue stirring for 2 to 3 minutes, then add the fine powder mixture obtained in step B and stir for 1 to 2 minutes, finally add the remaining composite plasticizer solvent and binder in turn, mix and grind for 10 to 15 minutes into a paste state, and thus obtain the wet plastic.

[0027] Example 4

[0028] A wet plastic material for a copper smelting system comprises the following raw materials by weight: 70 parts of a granular mixture, which is prepared by mixing alumina with Al2O3≥85% and particle sizes of 3-1mm and 0.1-1mm; 45 parts of a fine powder mixture, which is prepared by mixing alumina powder with a particle size of ≤74μm, plate-shaped corundum powder with a particle size of ≤44μm, Guangxi white mud and bentonite powder with a particle size of ≤74μm, aluminum oxide micropowder with Al2O3≥99% and a particle size D50, μm requirement of 2.3±0.5, and silicon carbide micropowder; 18 parts of a composite plasticizing solvent, which is prepared by mixing water, carboxymethyl cellulose, sodium tripolyphosphate, dextrin and benzoic acid; 12 parts of a binder, which is prepared by mixing phenolic resin and ethylene glycol; and 3 parts of an explosion-proof agent.

[0029] Experimental example Take an appropriate amount of wet plastic material for copper smelting system prepared in any embodiment and attach it to the copper melting furnace by extrusion or grouting as the furnace lining. The specific construction process is a conventional method in the art and will not be described in detail here. According to the usage, the usage information of the wet plastic material prepared in the embodiment and comparative examples 1 to 3 is recorded. The results are shown in Table 1. It can be seen from the results in Table 1 that the wet plastic material for the copper smelting system of the present invention fully meets the lining strength requirements of the copper smelting furnace, and not only has good high temperature resistance, corrosion resistance, and wear resistance, but also effectively prolongs the service life.

Claims

1. A wet plastic material for copper smelting system, characterized in that: The wet plastic material comprises the following raw materials by weight: 60 to 70 parts of granular mixture, 35 to 45 parts of fine powder mixture, 10 to 18 parts of composite plasticizing solvent, 5 to 12 parts of binder, and 0.5 to 3 parts of explosion-proof agent.

2. The wet plastic material for copper smelting system according to claim 1, characterized in that: The particle mixture is a mixed alumina with Al2O3≥85%, and the mixed alumina includes 30-35 parts of alumina with a particle size of 3-1 mm and 28-32 parts of alumina with a particle size of 0.1-1 mm.

3. The wet plastic material for copper smelting system according to claim 1, characterized in that: The fine powder mixture comprises: 11-13 parts of alumina powder, 11-13 parts of plate-shaped corundum powder, 5-8 parts of Guangxi white mud, 3-5 parts of bentonite powder, and 2-4 parts of alumina micropowder.

4. The wet plastic material for copper smelting system according to claim 3, characterized in that: The alumina powder particle size is ≤74μm, the plate-shaped corundum powder particle size is ≤44μm, the Guangxi white mud and bentonite powder particle size is ≤74μm, the alumina powder Al2O3 is ≥99%, and the particle size D50, μm requirement is 2.3±0.

5.

5. The wet plastic material for copper smelting system according to claim 1, characterized in that: The explosion-proof agent is explosion-proof fiber with a melting point of ≤105°C.

6. The wet plastic material for copper smelting system according to claim 1, characterized in that: The composite plasticizing solvent comprises 88 parts of water, 4-5 parts of carboxymethyl cellulose, 4-5 parts of sodium tripolyphosphate, 1-2 parts of dextrin and 1-2 parts of benzoic acid.

7. The wet plastic material for copper smelting system according to claim 1, characterized in that: The binder comprises 33 parts of phenolic resin and 67 parts of ethylene glycol.

8. The wet plastic material for copper smelting system according to claim 1, characterized in that: The fine powder mixture also includes 10 to 18 parts of silicon carbide powder.

9. The method for preparing wet plastic material for copper smelting system according to claim 1, characterized in that: The following steps are involved: A. Preparation of particle mixture: add alumina with a particle size of 3-1 mm and alumina with a particle size of 0.1-1 mm into a mixing mill and mix for 1-2 minutes for later use; B. Preparation of fine powder mixture: add special grade alumina powder, plate-shaped corundum powder, Guangxi white mud, bentonite powder, alumina powder and silicon carbide powder into a mixer and grind for 1-2 minutes for later use; C. Preparation of composite plasticizer solvent: Take room temperature water with 25% plasticizer solvent and add sodium tripolyphosphate, dextrin and benzoic acid in a container in turn, and stir until dissolved; secondly, add carboxymethyl cellulose and stir for 10-20 minutes, stir evenly, add boiling water with 63% plasticizer solvent, stir rapidly for 30-50 minutes until paste, cool for 1-2 hours, and set aside; D. Preparation of binder: put ethylene glycol in a container, add phenolic resin while stirring until the solution is uniform, and set aside; E. Preparation of wet plastic material: first place the granular mixture obtained in step A in a planetary mixer, add 30% to 40% of the total amount of the composite plasticizer solvent obtained in step C while stirring, then add 28 to 32% of the total amount of the binder obtained in step D and continue stirring for 2 to 3 minutes, then add the fine powder mixture obtained in step B and stir for 1 to 2 minutes, finally add the remaining composite plasticizer solvent and binder in turn, mix and grind for 10 to 15 minutes into a clay state, and thus obtain the wet plastic material.